A70 ASSOCIATION BETWEEN PROTON PUMP INHIBITOR USE IN HOSPITALIZED CIRRHOTICS AND DEVELOPMENT OF HEPATIC ENCEPHALOPATHY AND SPONTANEOUS BACTERIAL PERITONITIS. (26th February 2020) - Tan, P; Ukos, M; Miller, C; Lombardi, J; Kelly, E M
Abstract: Background: Proton pump inhibitors (PPI) are commonly prescribed medications which are indicated in various different gastrointestinal (GI) diseases, including peptic ulcer disease, gastroesophageal reflux disorder and upper GI bleeding. There is some evidence to suggest that PPI use in cirrhosis may predispose to the development of hepatic encephalopathy (HE) and spontaneous bacterial peritonitis (SBP), albeit with some controversy. Aims: We aim to conduct a retrospective epidemiological analysis of the association between PPI use in hospitalized patients with cirrhosis, and prevalence of HE and SBP. Methods: This was a retrospective cohort study of 600 adult patients (mean age 61.4 (SD=12.2)) admitted the Ottawa Hospital between January 1, 2011 and December 31, 2015 with cirrhosis. A chart review was conducted and relevant information extracted. Results: Average MELD-Na on admission was 16.2 (sd=6.7). 14.8% of patients had a history of HE, 5.0% SBP, 7.8% with history of hepatocellular carcinoma and 1.0% with history of hepatorenal syndrome. 28.5% of patients had a history of varices, of which 11.0% had previous variceal bleeding. 69.3% of patients were on a PPI during their hospitalization. Not surprisingly, patients admitted with variceal bleeding were more likely to be exposed to PPI in hospital (97.2% vs 63.2%, p<0.01) Patients with a diagnosis of cirrhosis prior to index admission were more likely to be on a PPI in hospital (p=0.001) and on discharge (p=0.001). Patients with ascites were less likely to be on a PPI than those without ascites (64.1% vs 77.6%, p<0.01). There was no significant correlation between in hospital PPI use and MELD score (p=0.42). Amongst patients on PPI in hospital, 85.9% remained on a PPI at discharge. Although numerically greater, no statistically significant differences were observed in terms of prevalence of HE (21.3% in patients on PPI vs 8.3% in those not on PPI (p=0.37)), nor SBP (5.7% on PPI vs. 3.7% in those not on PPI (p=0.29)). Conclusions: We did not observe a significant difference in HE and SBP among this cohort of cirrhotic patients by in-hospital PPI use. We did however note significantly higher PPI use in patients with previous diagnosis of cirrhosis as compared to those who were newly diagnosed, as well as those whose admissions were related to bleeding. Patients with ascites had lower prevalence of PPI use. Prescribing patterns for PPIs in patients with cirrhosis warrant further attention, including clinical utility and longer-term risks and benefits of this therapy. Funding Agencies: None